BIOGRAFI KH. MUNTAHA (1912-2004) SEBAGAI PEMIMPIN PONDOK PESANTREN AL-ASY’ARIYYAH WONOSOBO - Faisal Kamal; Abdurrahman Mas’ud; Nur Uhbiyati (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
This study aims to describe the biography and role of KH Muntaha in developing a boarding school education model that integrates general and religious education. This system turned out to have a positive impact on the progress of the al-Asy'ariyyah Islamic boarding school. This research uses historical, sociological, and anthropological approaches. Collecting data by in-depth interviews, observation, and documentation. KH Muntaha's thinking in integrating general and religious education has succeeded in bringing the progress of the al-Asy'ariyyah Islamic boarding school, which is evidenced by the rapid development of formal schools from the pre-school, elementary, secondary, and tertiary levels. In addition, the important contribution of KH. Muntaha's role in the development of Islamic boarding schools is that his thoughts are manifested in various educational innovations, such as the existence of a grading system, the inclusion of general education subjects, the development of management and bureaucratic leadership, the improvement of the functionality of Islamic educational institutions, institutions characterized by the study of the Qur'an study. 'an, the writing of the Mushaf al-Qur'an Akbar. The results and findings of this study indicate the contribution of KH. Muntaha is the main figure who determines the development of the al-Asy'ariyyah Islamic boarding school. These findings are important results that have implications for the development of education with an integrated model of educational institutions that can advance Islamic boarding schools al-Asy'ariyyah as Islamic educational institutions.